A tribute to Karen Greenwood and her contributions to the American Medical Informatics Association. (18th March 2022) - Lehmann, Christoph U; Brennan, Patricia F; Detmer, Don E; Jackson, Gretchen P; Ohno-Machado, Lucila; Safran, Charles; Williamson, Jeffrey J; Shortliffe, Edward H
Abstract: After 25 years of service to the American Medical Informatics Association (AMIA), Ms Karen Greenwood, the Executive Vice President and Chief Operating Officer, is leaving the organization. In this perspective, we reflect on her accomplishments and her effect on the organization and the field of informatics nationally and globally. We also express our appreciation and gratitude for Ms Greenwood's role at AMIA.